Extensive functional comparisons between chimeric antigen receptors and T cell receptors highlight fundamental similarities. (October 2021) - Wang, Xueyin; Martin, Aaron D.; Negri, Kathleen R.; McElvain, Michele E.; Oh, Julyun; Wu, Ming-Lun; Lee, Wen-Hua; Ando, Yuta; Gabrelow, Grant B.; Toledo Warshaviak, Dora; Sandberg, Mark L.; Xu, Han; et al.
Graphical abstract: Highlights: Compared multiple CARs to TCRs directed at the same targets in acute and long-term functional assays. CAR-Ts similar to TCR-Ts with regard to immune modulation in vitro: cytokine (IL-2), co-stimulation (CD28), checkpoint (PD-1). Implies commonality of signaling mechanisms for activation, proliferation, cytotoxicity. No intrinsic advantage to either receptor class for cell therapy with respect to activation or exhaustion. Abstract: Though TCRs have been subject to limited engineering in the context of therapeutic design and optimization, they are used largely as found in nature. On the other hand, CARs are artificial, composed of different segments of proteins that function in the immune system. This characteristic raises the possibility of altered response to immune regulatory stimuli. Here we describe a large-scale, systematic comparison of CARs and TCRs across 5 different pMHC targets, with a total of 19 constructs examined in vitro . These functional measurements include CAR- and TCR-mediated activation, proliferation, and cytotoxicity in both acute and chronic settings. Surprisingly, we find no consistent difference between CARs and TCRs as receptor classes with respect to their relative sensitivity to major regulators of T cell activation: PD-L1, CD80/86 and IL-2. Though TCRs often emerge from human blood directly as potent, selective receptors, CARs must be heavily optimized to attain these properties for pMHC targets. Nonetheless, when iteratively improved and compared head to head in functional tests, CARs appear remarkably similar to TCRs with respect to immune modulation.